Museums and the interpretation of visual culture - Hooper-Greenhill, Eilean, 1945- (London: Routledge, 2000)
This is a multi-disciplinary study that adopts an innovative and original approach to a highly topical question, that of meaning-making in museums.
CCS Gent
Includes bibliographical references (p. 176-190) and index.
boek
Keywords: Museums -- Philosophy; Museums -- Educational aspects; Museum exhibits; Visual communication; Visual learning; Visual perception; Communication and culture